2017
DOI: 10.1039/c7cp03052e
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation characteristics, water uptake and proton conductivity of composite Nafion membranes

Abstract: The free volumes and proton conductivities of Nafion membranes were investigated at different humidities by positron annihilation lifetime spectroscopy (PALS) and using an electrochemical workstation, respectively. The results showed that the variation in o-Ps lifetime τ was closely associated with the microstructure evolution and the development of hydrophilic ion clusters in Nafion membranes as a function of water uptake, regardless of metal oxide additives. In particular, with increasing relative humidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 61 publications
4
63
0
Order By: Relevance
“…21 Ionic conductivity enhancement with increased humidity level and the ionic Seebeck effect were recently reported for Na + ions in PEDOT:PSS. 5 Previously the effect of hydration level was mainly studied experimentally 22,23 and theoretically 24,25 in proton transport through hydrated Nafion for application in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…21 Ionic conductivity enhancement with increased humidity level and the ionic Seebeck effect were recently reported for Na + ions in PEDOT:PSS. 5 Previously the effect of hydration level was mainly studied experimentally 22,23 and theoretically 24,25 in proton transport through hydrated Nafion for application in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…PALS was then used to study the free volume of these membranes, with the o-Ps annihilation lifetime τ3 value providing a measure of their free volume element sizes and number densities [35]. Figure 4b shows the results obtained from the positron annihilation experiments of the pure Nafion, 5%@Nafion/SiO 2 @240°C, 5%@Nafion/SiO 2 @270°C, and 5%@Nafion/SiO 2 @300°C membranes.…”
Section: Resultsmentioning
confidence: 99%
“…As determined by positron annihilation spectroscopy, our initial study 41 showed that the mean diameter of the free volume holes of swollen Pd@CS membrane catalyst ranged from 0.5 to 1.2 nm, which is close to the size of the reactants as applied in Heck reaction. Moreover, previous studies [45][46][47][48][49][50] have demonstrated the free volume properties of the polymer membrane was the governing factor controlling the transport performances of gas (CO 2 ), water, solutes, and so on. Therefore, it is believed that the free volume holes of the polymer membrane could be the diffusion channels for the reactants.…”
Section: Introductionmentioning
confidence: 99%